Three‐dimensional static optical coherence elastography based on inverse compositional Gauss‐Newton digital volume correlation - Meng, Fanchao; Chen, Cheng; Hui, Shun; Wang, Jingbo; Feng, Yvlong; Sun, Cuiru (Journal of biophotonics, 2019)
The three‐dimensional (3D) mechanical properties characterization of tissue is essential for physiological and pathological studies, as biological tissue is mostly heterogeneous and anisotropic. A digital volume correlation (DVC)‐based 3D optical coherence elastography (OCE) method is developed to measure the 3D displacement and strain tensors. The DVC algorithm includes a zero‐mean normalized cross‐correlation criterion‐based coarse search regime, an inverse compositional Gauss‐Newton fine search algorithm and a local ternary quadratic polynomial fitting strain calculation method. A 3D optical coherence tomography (OCT) scanning protocol is proposed through theoretical analysis and experimental verification. Measurement errors of the DVC‐based 3D OCE method are evaluated to be less than 2.0 μm for displacements and 0.30% for strains by rigid body motion experiments. The 3D displacements and strains of a phantom and a specimen of chicken breast tissue under compression are measured. Results of the phantom show a good agreement with theoretical analysis and tensile testing. The strains of the chicken breast tissue indicate anisotropic biomechanical properties. This study provides an effective method for 3D biomechanical property studies of soft tissue and improves the development of 3D OCE techniques. A three‐dimensional (3D) optical coherence elastography (OCE) technique is developed by integrating a specific coarse‐fine search digital volume correlation (DVC) algorithm and an optical coherence tomography (OCT) imaging. A guidance for choosing the optimal number of OCT line scans is proposed by theoretical analysis and experimental verification. This DVC‐based OCE method has the potential for high accurate 3D displacement and strain tensor measurement of heterogeneous and anisotropic biological tissue.